2021
DOI: 10.1007/978-1-0716-1892-9_13
|View full text |Cite
|
Sign up to set email alerts
|

Glucan Particles: Choosing the Appropriate Size to Use as a Vaccine Adjuvant

Abstract: Beta-glucans are a group of polysaccharides with intrinsic immunostimulatory properties which makes the design of new particulate vaccine adjuvants based on β-glucans very promising. The size of the particles and the antigen loading method, encapsulated into particles or adsorbed on its surface, will influence the toxicological and adjuvanticity properties of the particulate adjuvant. Herein we describe the production of glucan nanoparticles (NPs) with three different sizes, approximately 150 nm, 350 nm, and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Notably, β-glucans specifically identifies macrophages and has been used to transfer payload macromolecules; that is, protein (21,22), deoxyribonucleic acid (DNA) (23,24), small-interfering ribonucleic acid (25), and small drug molecules (e.g., rifampicin, methotrexate, and curcumin] (26-28). They have also been studied in the context of hepatitis B therapy (29), Francisella vaccines (30), and as a new tool in vaccine development (31,32). We p r e v i o u s l y r e p o r t e d c h a n g e s i n t h e b a s i c morphological structure of the tissue surrounding the liver lesions of secondary hydatid mice, and found that the basic morphological structure of the tissues surrounding the hepatic alveolar hydatid lesions changed, and a large number of inflammatory cells were infiltrated around the central veins and portal areas.…”
Section: What Is the Implication And What Should Change Now?mentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, β-glucans specifically identifies macrophages and has been used to transfer payload macromolecules; that is, protein (21,22), deoxyribonucleic acid (DNA) (23,24), small-interfering ribonucleic acid (25), and small drug molecules (e.g., rifampicin, methotrexate, and curcumin] (26-28). They have also been studied in the context of hepatitis B therapy (29), Francisella vaccines (30), and as a new tool in vaccine development (31,32). We p r e v i o u s l y r e p o r t e d c h a n g e s i n t h e b a s i c morphological structure of the tissue surrounding the liver lesions of secondary hydatid mice, and found that the basic morphological structure of the tissues surrounding the hepatic alveolar hydatid lesions changed, and a large number of inflammatory cells were infiltrated around the central veins and portal areas.…”
Section: What Is the Implication And What Should Change Now?mentioning
confidence: 99%
“…Notably, β-glucans specifically identifies macrophages and has been used to transfer payload macromolecules; that is, protein ( 21 , 22 ), deoxyribonucleic acid (DNA) ( 23 , 24 ), small-interfering ribonucleic acid ( 25 ), and small drug molecules (e.g., rifampicin, methotrexate, and curcumin] ( 26 - 28 ). They have also been studied in the context of hepatitis B therapy ( 29 ), Francisella vaccines ( 30 ), and as a new tool in vaccine development ( 31 , 32 ).…”
Section: Introductionmentioning
confidence: 99%
“…Another significant effect is that they prevent fat absorption from food and stabilizing blood sugar (glucose) levels after consumption [ 3 , 23 ]. Due to the immunostimulatory properties of β-glucans, the planning of vaccine adjuvants based on β-glucans is an interesting perspective [ 24 ]. Mushrooms are an interesting component of human nutrition due to all of these properties and their high content of essential nutrients such as proteins, polysaccharides, and lipids [ 25 ].…”
Section: Introductionmentioning
confidence: 99%